A preliminary study on the effect of nest exploitation to reproduction of edible-nest swiftlet species population Aerodramus fuciphagus (Thunberg, 1812) in Cu Lao Cham nature reserve, Quang Nam province - Phong, Vo Tan; Thuy, Le Dinh; Phuong Anh, Dinh Thi (Academia Journal of Biology, 2015)
The Cu Lao Cham natural reserve is  the house of one population of edible-nest swiftlet species, Aerodramus fuciphagus, which nested in the caves of islands with thousands of individuals. The nest exploitation of  edible-nest swiftlet species is the one of economic sectors that gives the high income for Quang Nam province. However, the nest exploitation has some effects on reproductiion of edible-nest swiftlet species. Our research on the effect of nest exploitation on  reproduction of Swiftlet was carried out during  2012 and 2013 years. The  result of our research showed that, in the condition without nest exploitation, Aerodramus fuciphagus nested two times per year, i,e. about 53.9% total of females repeatedly nested in the second time in a year The rate of immature birds left nests made in the second time is lower than that made in the first time. In the condition with nest exploitation of  two times per year, rate of immature birds left nests made in the first time, and adult birds repeatedly nested in the second time depended on the first time nest exploitation. Generally, the measure and weight of nests made in the  second time are  lesser than that made in the first time.